Nutritional intervention for cancer sarcopenia - Takuya Mori; Akira Kido; Isao Kawahara; Shota Nuaga; Yoshihiro Miyagawa; Kei Goto; Shiori Mori; Shingo Kishi; Kiyomu Fujii; Rina Fujiwara-Tani; Hiroki Kuniyasu (Annals of Musculoskeletal Medicine - Peertechz Publications, 2021)
Most patients with advanced cancer develop skeletal muscle atrophy called sarcopenia, which reduces treatment tolerance and social activity and worsens the prognosis. Glucose suppresses skeletal muscle atrophy in cancer-bearing mice, while promoting cancer growth. In contrast, medium-chain fatty acids reduce skeletal muscle atrophy and suppress cancer growth. Simultaneous administration of glucose and medium-chain fatty acids suppresses skeletal muscle atrophy and eliminates the tumor growth seen in glucose. Based on these findings, dietary intervention using a combination of glucose and medium-chain fatty acids is expected to be effective in suppressing sarcopenia in cancer patients.